(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
In this paper, a fuzzy logic controller determines the turning ON or OFF of a power supply in a scalable n-parallel power supply configuration. Each power supply is modeled using differential equations and only differs in the values of its parasitic resistances. This is done in a MATLAB/Simulink environment. A fuzzy logic controller accepts the power supply usage and the power supply’s input voltage perturbation as its inputs while the probability of the corresponding power supply turning ON is its output. The power supplies are connected in parallel configuration and tested under various conditions of static and dynamic current sharing load, voltage input perturbations and on the total number of active power supplies in a given parallel configuration. The number of power supplies n in the parallel configuration is changed by adding or removing a power supply. This addition or removal is termed as scalability. As a result, the fuzzy logic controller was able to guarantee that all power supplies in the scalable n-parallel configuration have equal usage while sharing the load current equally under a regulated output voltage.